The impact of infrastructure development on economic growth in sub-Saharan Africa with special focus on Ghana. Issue 3 (4th November 2019) - Owusu-Manu, De-Graft; Jehuri, Adam Braimah; Edwards, David John; Boateng, Frank; Asumadu, George
Abstract : Purpose: This paper aims to assess the impact of infrastructure development on Ghana's economic growth. Design/methodology/approach: Using data obtained from the World Bank's World Development Indicators, the United States' (US) International Energy Statistics and the Central Intelligence Agency's (CIA) Factbooks from 1980 to 2016, an autoregressive distributed lag (ARDL) framework is used to determine the long- and short-run impact of the selected infrastructure stock and quality indices on Ghana's economic growth. Findings: Findings indicate a statistically significant relationship between infrastructure development and economic growth. Additionally, electricity-generating capacity is identified as the infrastructure stock index that has the greatest positive impact on Ghana's economic growth. The study reveals that electricity-distribution loss has a significant negative effect over both long- and short-run periods. Research limitations/implications: Commercial petroleum export from Ghana since 2010 has been a key contributor to economic growth. Although its aggregate effect is included in the annual GDP figures adopted for the study, the authors would have wished to assess its impact on GDP as an independent standard growth determinant. However, because of a lack of available data over this study period, petroleum exports could not be adopted as an independent standard growth determinant. Additionally, an aggregated index of infrastructure stock and quality could not be derived because of the small size of data available. Hence, this study did not assess its impact on Ghana's economic growth. Practical implications: The research provides pragmatic guidance to policymakers to focus their efforts on expanding electricity-generating capacity while simultaneously taking steps to curb electricity transmission and distribution losses. These two related actions offer the greatest positive impact on infrastructure development and, as a consequence, Ghana's economic growth. Originality/value: This paper represents the first attempt to empirically study the relationship between infrastructure development and Ghana's economic growth. A key contribution to the existing body of knowledge includes strong evidence of a positive effect of infrastructure development upon Ghana's economic growth. Results also reveal that the greatest positive impact on economic growth is derived from electricity-generation capacity. However, the study also uncovers a negative, but statistically significant, relationship between road and economic growth.